Social Economy, Entrepreneurship and local development: the case of 'Arcturos' environmental centre - Margarita Trikka; Georgia Charitoudi (European Regional Science Association (ERSA), 2013)
The concept and the activities of social economy are not particularly developed in Greece. Several institutions have made some attempts to change that during the past few years but they failed due to the lack of the proper and flexible institutional frame that would administratively and financially support the initiatives. The domain of Social Economy in Greece has not been acknowledged as such, even though there is a considerable number of institutions that operate under its roof. Generally, the Greek society tends to attach to such initiatives a notion of ?charity?. There are three main advantages of the social enterprises, according to the literature and the European experience: ? Support of local development ? New products and services offered ? Employment for people that face difficulties Research on the third system has proved that its approach present a number of advantages compared to the public or private profit-oriented domain. It also has a positive impact on employment and on the important aspects of social and economic life. This is true especially on a local level as it improves the quality of life, it develops new economic factors, it enhances the social bonds and the social unity and it boosts creativeness and innovativeness. In order to examine the role and contribution of social enterprises in the local development, an empirical research was realized in November 2012. The field of the research was the Municipality of Amyntaio, where the social enterprise ?ARCTUUROS Environmental Centre? is situated. ARCTUROS is a Greek, non-governmental organization seeking to enhance biodiversity and sustainability in the Greek rural areas. ARCTUROS implements cross-border projects in order to protect mountainous ecosystems, with an emphasis on bears and large mammals, aiming at the integrated management of protected mountainous regions and the provision of expertise for natural environment interventions. ARCTUROS Environmental Center resolved the problem of captive bears and wolves in Greece and raised public awareness about large mammals. ARCTUROS is a non-profit civil partnership that lobbies to protect nature by developing actions of public awareness, environmental education and volunteerism. The research was realized through structured questionnaires the examination of which, leads us to interesting conclusions about the impact of a social enterprise on remote and disadvantaged areas.
Keywords: R11; P31; Q56; 330; Social Economy; Social entrepreneurship; local development; ?Arctouros?; Greece